Large mirrors and telescopes : 4th International Symposium on Advanced Optical Manufacturing and Testing Technologies : 19-21 November 2008, Chengdu, China - International Symposium on Advanced Optical Manufacturing and Testing Technologies (4th : 2008 : Chengdu, China); Jiang, Wenhan, 1936-; Zhongguo guang xue xue hui; Zhongguo ke xue yuan. Institute of Optics and Electronics; SPIE (Society); State Key Laboratory of Optical Technology for Microfabrication (China); Sichuan Optical Society; Zhongguo guang xue xue hui. Committee of Optical Manufacturing Technology; Guo jia zi ran ke xue ji jin wei yuan hui (China); Zhongguo ke xue yuan (Bellingham, Wash. : SPIE)
Includes bibliographical references and author index